2001
DOI: 10.1002/j.2048-7940.2001.tb01959.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Disease-Modifying Therapy in Multiple Sclerosis: Part II

Abstract: Multiple sclerosis (MS) is a chronic, debilitating disease for which there is no cure; however, the recent introduction of injectable immunomodulating agents has reduced the rate of relapsing episodes and possibly slowed the progression of the disease. These disease-modifying agents are recommended by the National MS Society, but their true potential cannot be realized if patients do not accept them and healthcare professionals do not promote them. Since MS has an unpredictable course, and treatments can produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…However, these authors did not specifically address the influence of nurse support on treatment adherence, as it was the case in the present study. When this parameter was specifically addressed a positive effect of MS nurses on MS treatment adherence was documented [7,31].…”
Section: Discussionmentioning
confidence: 99%
“…However, these authors did not specifically address the influence of nurse support on treatment adherence, as it was the case in the present study. When this parameter was specifically addressed a positive effect of MS nurses on MS treatment adherence was documented [7,31].…”
Section: Discussionmentioning
confidence: 99%
“…The TTM has been used to develop a variety of instruments that measure readiness stage and evaluate the effectiveness of interventions to accelerate healthy changes such as adherence to exercise programs, smoking cessation, weight reduction, and safer sex practices [20,21]. Although the TTM has also been previously adapted to facilitate readiness for treatment of MS with disease-modifying therapies [23], our intent was to focus on a single behavior within the realm of MS treatment, that being the readiness to administer daily self-injections. Table 1 summarizes the stages of readiness and processes of change for adopting self-injection that were developed for this study.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that DMT might not be effective in those patients with a poor level of adherence in the long term [2]. According to different authors, the main factors that contribute to whether the patient is adherent are related to perceived lack of efficacy, lack of information or too complex information, false hopes of improvement in the disease, problems administering treatment (such as fear of needles or self-injections) and sociocultural factors [8,9]. …”
Section: Introductionmentioning
confidence: 99%